2001
DOI: 10.1016/s0886-3350(01)00925-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of corneal endothelial density over a lifetime

Abstract: Knowing the representative values of endothelial density and the probabilities of occurrence over a lifetime can help surgeons determine the risk to the cornea of anterior segment surgery. It can also be useful in following eyes with disease affecting the endothelium and in preparing and evaluating corneal specular microscopy reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 10 publications
8
47
1
9
Order By: Relevance
“…A signifi cant difference was observed between groups immediately after surgery (G1=23.4±9.74; G2=46.0±9.04), day 7 (G1=18.9±7.72; G2=45.6±5.19), day 30 (G1=15.5±9.01; G2=61.1±3.69), day 45 (G1=14.5±7.98; G2=62.4±3.41) and day 60 (G1=28.3±10.15; G2=70.8±4.06) after phacoemulsifi cation. RODRIGUES (1999) and ABIB & BARRETOS (2001) showed that corneal cell density decreases with age. Besides aging infl uence, several factors, such as trauma and intraocular infl ammation, may lead to endothelial loss (TUFT & COSTER, 1990;PIGATTO et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…A signifi cant difference was observed between groups immediately after surgery (G1=23.4±9.74; G2=46.0±9.04), day 7 (G1=18.9±7.72; G2=45.6±5.19), day 30 (G1=15.5±9.01; G2=61.1±3.69), day 45 (G1=14.5±7.98; G2=62.4±3.41) and day 60 (G1=28.3±10.15; G2=70.8±4.06) after phacoemulsifi cation. RODRIGUES (1999) and ABIB & BARRETOS (2001) showed that corneal cell density decreases with age. Besides aging infl uence, several factors, such as trauma and intraocular infl ammation, may lead to endothelial loss (TUFT & COSTER, 1990;PIGATTO et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…The structure of the normal corneal endothelium has been documented in humans (ABIB & BARRETO, 2001), dogs (GWIN et al, 1982;PIGATTO et al, 2006;RODRIGUES et al, 2006), horses (ANDREW et al, 2001) and other animal species (YEE et al, 1987;COLLIN & COLLIN, 1998;PIGATTO et al, 2004;PIGATTO et al, 2005a;PIGATTO et al, 2005b). The ostrich (Struthio camelus) is the world's largest living bird.…”
Section: Objetivoumentioning
confidence: 99%
“…Due to the fact that there is no cellular retraction and it can be used in animals and living humans, specular microscopy is considered the gold standard technique for assessing the corneal endothelium in people and animals (MORITA, 1995;ABIB & BARRETO, 2001;PIGATTO et al, 2006;PIGATTO et al, 2008;FRANZEN et al, 2010;BERCHT et al, 2015;ALBUQUERQUE et al, 2015;COYO et al, 2016). Specular microscopy has also been employed in the evaluation of dogs undergoing cataract removal surgery (NAGATSUYU et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the present study was to evaluate the cell density and percentage of hexagonal cells because these are the most reliable parameters for evaluating the integrity of the corneal endothelium (ABIB & BARRETO, 2001;PIGATTO et al, 2006;NAGATSUYU et al, 2014). SAILSTAD and PEIFFER (1981) observed the corneal endothelium of 14 young adult rabbits using a specular microscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation